2022
DOI: 10.48550/arxiv.2204.07607
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anomalous Hall conductivity control in Mn$_3$NiN antiperovskite by epitaxial strain along the kagome plane

Abstract: Antiferromagnetic manganese-based nitride antiperovskites, such as Mn3NiN, hold a triangular frustrated magnetic ordering over their kagome lattice formed by the Mn atoms along the (111)plane. As such, frustration imposes a non-trivial interplay between the symmetric and asymmetric magnetic interactions, which can only reach equilibrium in a noncollinear magnetic configuration. Consequently, the associated electronic interactions and their possible tuning by external constraints, such as applied epitaxial stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…Evidently, this value is considerably smaller than the reported one. For example, in the Mn 3 NiN case, D. Torres-Amaris et al [51] showed that under the PBEsol+U scheme, as shown here, the AHC is σ xy = 68 S•cm −1 , in better agreement with the experimentally reported value of σ xy = 22 S•cm −1 in thin-films [67], and considerably smaller than the calculated value of σ xy = 130-170 S•cm −1 in Refs. [67,68] where no correction was considered.…”
Section: Introduction-supporting
confidence: 88%
See 2 more Smart Citations
“…Evidently, this value is considerably smaller than the reported one. For example, in the Mn 3 NiN case, D. Torres-Amaris et al [51] showed that under the PBEsol+U scheme, as shown here, the AHC is σ xy = 68 S•cm −1 , in better agreement with the experimentally reported value of σ xy = 22 S•cm −1 in thin-films [67], and considerably smaller than the calculated value of σ xy = 130-170 S•cm −1 in Refs. [67,68] where no correction was considered.…”
Section: Introduction-supporting
confidence: 88%
“…Thus, as indicated by our results and by W. Rieger et al [44], such an Au-centered structure is considerably higher in energy, and the N-centered structure is potentially the crystallographic ground state. As observed in the Mn 3 NiN antiperovskite, it is recommended to correct the electronic exchange-correlation by including the Coulomb U repulsion parameter in the magnetically active cation to adequately reproduce the vibrational, structural, and electronic degrees of freedom in the V 3 AuN [6,51]. Along these lines, we have fully relaxed the electronic and atomic structure of the V 3 AuN compound within the metaGGA SCAN-based exchangecorrelation [33] and we obtained a relaxed lattice parameter of 3.961 Å in good agreement with the experimentally reported value of a = 3.962 Å [44].…”
Section: Introduction-mentioning
confidence: 99%
See 1 more Smart Citation